Availability and Problems Relating to the Accessibility of Information and Communication Technologies (ICT’s) Among University Students: Mahek Arshad,Quratul Ain Hina (PJDOL, 2023)
Information and Communication Technologies plays an important role in today’s information societies and educational systems of nations. Information and Communication Technologies are of greatest significance for the future of education in Pakistan. The major purpose of the study was to explore the availability and problems relating to the accessibility of Information and Communication Technologies (ICT’s)among university students.